A Comprehensive Literature Review of Aldosterone Antagonist Therapy and Mortality in Patients With ST-Segment Elevation Myocardial Infarction Without Heart Failure - Zulkarnain, Zulkarnain; Yogi, Yogi; Elizabeth, Elizabeth (The International Journal of Medical Science and Health Research, 2024)
Background: The literature review presents a comprehensive analysis of aldosterone antagonist therapy in the context of ST-segment elevation myocardial infarction (STEMI) among patients without heart failure. The introduction highlights the significance of the renin-angiotensin-aldosterone system (RAAS) and its impact on cardiovascular health, particularly in acute myocardial infarction scenarios. Literature Review: The main body of the review discusses several key studies that examine the effectiveness and safety of aldosterone antagonists in STEMI patients. The findings from (M Nappi & Sieg, 2011) emphasize the adverse effects of RAAS, while studies such as (Y. Wang et al., 2016) and (Pitts et al., 2017) suggest that the mortality benefits of aldosterone antagonists may not extend to patients without heart failure. The meta-analysis by (Beygui et al., 2018) further supports the notion that mineralocorticoid receptor antagonists (MRAs) can reduce mortality in STEMI patients, indicating their potential utility even in the absence of overt heart failure. Conclusion: In conclusion, the literature presents a nuanced perspective on the role of aldosterone antagonists in managing STEMI patients without heart failure. While there is substantial evidence supporting their efficacy in heart failure contexts, the implications for patients without heart failure remain less clear. The existing studies indicate that while these agents may offer some benefits, their overall impact on mortality in this specific demographic is limited. Further research, particularly well-designed randomized trials, is essential to elucidate the therapeutic potential of aldosterone antagonism in improving outcomes for patients who experience myocardial infarction without concurrent heart failure.